Micro-Shopping and Omnichannel Adoption: Evidence on Market Structure and Competition in Indonesia Retail Eco-system - Ossi Ferli; Adelya Vasya Maharani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study examines the implications of the micro-shopping phenomenon and omnichannel integration for market structure and competitive dynamics in Indonesia’s retail sector from an industrial organization perspective. The transformation of modern retail is characterized by a shift toward small-value, high-frequency transactions alongside increasing integration between physical stores and digital channels. Employing a descriptive-analytical approach, this study utilizes secondary data on market shares and the number of retail outlets operated by major firms during the 2022–2024 period. Market structure is assessed through market share distribution, outlet ownership ratios, the four-firm concentration ratio (CR4), and the Herfindahl–Hirschman Index (HHI). The results indicate that Indonesia’s retail market exhibits a highly concentrated, network-based oligopolistic structure. The dominance of large retail firms is reflected not only in their substantial market shares but also in their dense outlet networks, which enable the aggregation of dispersed micro-shopping transactions. Furthermore, omnichannel integration reinforces these structural advantages by enhancing logistical coordination and distribution efficiency. Overall, the findings suggest an increasing tendency toward market consolidation and a declining competitive space for small and traditional retailers, highlighting important implications for competition policy and the long-term sustainability of retail market structure.